PERTANGGUNGJAWABAN TINDAK PIDANA TERHADAP PELAKU TINDAK PIDANA PERCOBAAN PEMBUNUHAN PUTUSAN NOMOR 45/PID.B/2021/PNSIM : Accountability For The Persons of The Criminal Action of Attempted Murder Decision Number 45/PID.B/2021/PN.Sim - Sabila Ridwan; Vientje Ratna Multiwijaya (AMICUS CURIAE, 2024)
Criminal responsibility for attempted murder is the ability legally to be accountable for their actions and to be aware that what they did was a violation. The perpetrator swung the machete, kicked and choked the victim but the execution was not completed because the perpetrator's mother came and pulled the perpetrator's hand from the victim's neck. The problems in this research are 1). Is the responsibility of the perpetrators of the attempted murder appropriate according to Article 351 paragraph (1) of the Criminal Code? and 2). Is the Judge's Decision Number 45/Pid.B/2021/PNSim which imposes a 2-year sentence on the perpetrator in accordance with the purpose of sentencing? This research was conducted using a normative legal research type that is descriptive in nature, using primary legal materials and secondary legal materials by collecting data from literature studies which were analyzed qualitatively and drawing conclusions using deductive logic. The conclusions from this study are (1). The criminal responsibility for the perpetrators of the attempted murder is not appropriate according to Article 351 paragraph (1) of the Criminal Code (2). The decision of the Panel of Judges Number 45/Pid.B/2021/PNSim for the perpetrators is not yet 2 years in prison according to the theory of sentencing purposes. The results of the research are related to the theory of sentencing purposes, so it should be subject to Article 338 in conjunction with Article 53 paragraph (1) of the Criminal Code with a sentence of 10 years in prison.